EVALUATION OF THE CENTER OF SPORTS EDUCATION AND TRAINING FOR STUDENTS (CSETS) PROGRAMS IN SOUTH SULAWESI, WEST SUMATERA, AND CENTRAL JAVA - Yunus, Muhammad; KS, Soegiyanto; Setiono, Hari (Universitas Negeri Semarang, 2017)
This study is meant to evaluate the implementation of the programs in CSETS of South Sulawesi, West Sumatera, and Central Java by using a CIPP method. This is an evaluation study by adopting a quantitative and qualitative approach. The data were collected by using questionnaires, interviews, documents and observation. The results show that in general, based on CIPP aspects, the programs of CSETS in three provinces are categorized to be good, with Central Java as the best, followed by West Sumatera and South Sulawesi. With the context aspect, all CSETS are categorized to be good, with Central Java as the best, followed by West Sumatera and South Sulawesi. With the input aspect, all CSETS are categorized to be good, with Central Java as the best, followed by South Sulawesi and West Sumatera. With the process aspect, CSETS of Central Java and West Sumatera are categorized to be good, and CSETS of South Sulawesi is categorized to be fair, with Central Java as the best, followed by West Sumatera and South Sulawesi. With the product aspect, CSETS of Central Java is categorized to be good, and CSETS of South Sulawesi and West Sumatera are categorized to be fair, with Central Java as the best, followed by South Sulawesi and West Sumatera.